2017
DOI: 10.13057/nusbiosci/n090313
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Infraspecific variations in essential oil compositions of Nepeta fissa from Iran

Abstract: Talebi SM, Nohooji MG,Yarmohammadi M. 2017. Short Communication: Infraspecific variations in essential oil compositions of Nepeta fissa from Iran. Nusantara Bioscience 9: 318-321. Nepeta fissa C.A. Mey. is a member of Mint family (Lamiaceae) and distributed naturally in different regions of Iran. The aim of this investigation was to provide more information about the influence of environmental conditions on the essential oil composition of two populations, Polor and Dizin, of this species. The dry plant sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our findings agreed with previous investigations on the essential oil compositions from this species. For example, Talebi et al (2017) examined essential oil compositions of two populations (Polor and Dizin) of this species. In Polor samples, the main constituents of oil were: phytol (20.0%), caryophyllene oxide (8.3%) and β-caryophyllene (7.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings agreed with previous investigations on the essential oil compositions from this species. For example, Talebi et al (2017) examined essential oil compositions of two populations (Polor and Dizin) of this species. In Polor samples, the main constituents of oil were: phytol (20.0%), caryophyllene oxide (8.3%) and β-caryophyllene (7.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the effect of altitude on the variations in essential oil compositions of three Nepeta species: N. sessilifolia, N. heliotropifolia, and N. fissa. Almost all previous studies on the essential oils of these species (Baser et al, 2000;Sajjadi & Khatamsaz, 2001: Jamzad et al, 2008Batooli & Safaei-Ghomi, 2012;Yarmohammadi et al, 2017;Talebi et al, 2017) were based on one mixed collective plant sample from one or two populations. By this way, we obtain a general picture of essential oil composition of these plants, and we lack the information about the chemical variability of its populations along the altitude gradient.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the determination of bioactive phytochemical constituents from different natural plant species [7][8][9][10]. However, the best of our knowledge there is no report about Nepeta nuda subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Poverene et al 2002;Talebi et al 2017) have revealed that different populations of the same species show variations in life cycles, height, leaf shape and phytochemical characteristics under different ecological conditions. These conditions could be led to creation of ecotypes and chemotypes in response to ecological and environmental constraints of different habitats (Richards et al 2006).…”
Section: Introductionmentioning
confidence: 99%